Docetaxel-loaded exosomes for targeting non-small cell lung cancer: preparation and evaluation in vitro and in vivo - Ying Wang; Mimi Guo; Dingmei Lin; Dajun Liang; Ling Zhao; Ruizhi Zhao; Yan Wang (Taylor & Francis Group, 2021)
Non-small cell lung cancer (NSCLC) is a highly lethal disease and the majority of NSCLC patients are desperate for therapies that can effectively target their cancer and ultimately improve their overall survival. Docetaxel (DTX) represents the first-line of the antitumor agent that is used to treat NSCLC; however, it has poor solubility in water and unsatisfactory encapsulation efficiency. In our study, exosomes were isolated from A549 cancer cells by ultracentrifugation and then characterized using transmission electron microscopy (TEM), nanoparticle tracking analysis (NTA), and Western blot (WB). The particle size changes of EXO and EXO-DTX were measured daily for seven days to test the stability. DTX was selected payload by electroporation (EXO-DTX). For the in vitro evaluation, cell proliferation, cell cycle, cell apoptosis, reactive oxygen species (ROS) assay and cellular uptake were evaluated in the A549 cells. Also, this study evaluated the target and therapeutic effect of DTX as an antitumor agent in vivo. As a result, EXO-DTX with a particle size of 149.5 nm were successfully prepared and the cytotoxicity of the EXO-DTX was much greater than that of DTX monomers. Exosomes significantly increased the cellular uptake in vitro evaluation and showed better targeting to tumor tissue compared to the free DTX in the mice. We also explored the potential of tumor cell-derived exosomes as a drug delivery agent to target the parent cancer. Hence, we conclude that exosomes might be used as a potential antitumor drug delivery system (DDS).